Control/ownership structure, creditor rights protection, and the cost of debt financing: International evidence - Boubakri, Narjess; Ghouma, Hatem (Journal of Banking & Finance, 2010)
We explore the effect of governance on bond yield-spreads and ratings in a multinational sample of firms. We find strong evidence that ultimate ownership (i.e., the voting/cash-flow rights wedge) and family control have a positive and significant effect on bond yield-spreads, and a negative and significant effect on bond ratings. Control in the hands of widely held financial firms has a positive effect on bond ratings only, while State control has no effect on either bond yield-spreads or ratings. We also find that a higher protection of debtholders’ rights generally reduces bond yield-spreads and increases bond ratings. Our results additionally show that, for both bondholders and rating agencies, the enforcement of debt laws is crucially important. Finally, we document a negative effect of debt covenants on debt costs when there is a high expropriation risk and poor creditor rights protection.